FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN ELECTRONIC WALLET (E-WALLET) DI MASYARAKAT: STUDI KASUS PADA PERAWAT DI RUMAH SAKIT SRIWIJAYA KOTA PALEMBANG - A. Glenntiko Wiratama Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to: (1) determine the factors that influence the use of electronic wallets at the Sriwijaya Hospital, Palembang City. (2) determine the most dominant factor in influencing the use of electronic wallets The research method used is quantitative research with a descriptive approach. Data obtained directly from respondents using questionnaire instruments), documentation, and observation.The results of this study indicate that the variables of trust, perceived security, perceived benefits, perceived convenience, perceived risk, consumptive behavior after being assumed using univariate, bivariate, and multivariate analysis are known to have a relationship to the use of electronic wallets. While the results of the multivariate analysis state that perceived security and perceived benefits have a significant effect on the use of electronic wallets.This then becomes the basis of information and policy considerations for related parties to further improve the governance system for the existence and use of electronic wallets, especially at the Faculty of Economics as well as Malang City, Palembang and the State of Indonesia in general. Therefore, the results of this research are then expected to be able to provide references for improvement in order to create professional work and fair welfare for all parties.